Perlindungan Konsumen Terhadap Penumpang Tanpa Kursi di Kereta Api Srilelawangsa dalam Perspektif Mashlahah Mursalah - Khairunnisa Harahap; Abd Rahman Harahap (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research is motivated by the injustice in Srilelawangsa train services, such as the lack of safety and comfort facilities for passengers who have to stand, including pregnant women, the elderly, and young people, which is an urgent problem to be addressed. This research aims to analyze the policies and implementation of consumer protection for standing passengers on the Srilelawangsa Train service by using an empirical legal method that combines a statute approach and a case approach. The statute approach is employed to examine regulations related to consumer protection, such as Law Number 8 of 1999 on Consumer Protection and applicable railway regulations. The case approach is used to analyze real conditions observed in the field regarding services for standing passengers, utilizing primary data obtained through direct observation and interviews with passengers and related parties involved with the Srilelawangsa Train service. Secondary data are sourced from legal literature, statutory regulations, and Islamic jurisprudence books related to the concept of Maslahah Mursalah. The research findings indicate that standing passengers have not received adequate protection, either from the perspective of positive law or the principle of public interest (Maslahah) in Islam. The lack of clear ticket information, the absence of supporting facilities such as handrails, and the weak enforcement of priority seating policies illustrate that consumer protection in this matter remains suboptimal. From the perspective of Maslahah Mursalah, the existing policies are considered to bring more harm than benefit to passengers and are therefore not justifiable under Islamic law. The conclusion of this research emphasizes the need for policy evaluation and the improvement of consumer protection through fair solutions grounded in the principles of Maslahah that prioritize passenger safety and comfort.